2003
DOI: 10.1029/2002tc001361
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate strike‐slip faulting along the Bangong‐Nujiang suture zone accommodates coeval east‐west extension and north‐south shortening in the interior of the Tibetan Plateau

Abstract: Geologic investigations of how the Tibetan plateau is currently deforming have focused primarily on its boundary faults. Consequently, how the interior of the plateau deforms remains poorly understood. To fill this gap in knowledge, we conducted field mapping, analysis of remote sensing and digital topographic data, and reinterpretation of existing geologic maps in central Tibet. This study reveals a 200–300 km wide and 1500–1800 km long east trending zone conjugate strike‐slip faults across central Tibet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
326
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(340 citation statements)
references
References 57 publications
7
326
1
Order By: Relevance
“…These are reflected along a slight relative eastwest topographic low by NE-SW left-lateral strike-slip faults that lie just north of the Bangong-Nujiang suture in the Qiangtang terrane and are also kinematically linked to the north with further north-south-oriented normal faults (Yin et al 1999). This pattern of faulting indicates a 250 km by 1500 km east-west-trending zone of conjugate strike-slip faulting across central Tibet that simultaneously accommodates north-south contraction and east-west extension (Taylor et al 2003). By mapping three of the fault systems, Taylor et al (2003) found average offsets in Tertiary thrusts and Palaeozoic-Mesozoic lithological units of only 12 km.…”
Section: Conjugate Strike-slip Faults Of Central Tibetmentioning
confidence: 99%
See 4 more Smart Citations
“…These are reflected along a slight relative eastwest topographic low by NE-SW left-lateral strike-slip faults that lie just north of the Bangong-Nujiang suture in the Qiangtang terrane and are also kinematically linked to the north with further north-south-oriented normal faults (Yin et al 1999). This pattern of faulting indicates a 250 km by 1500 km east-west-trending zone of conjugate strike-slip faulting across central Tibet that simultaneously accommodates north-south contraction and east-west extension (Taylor et al 2003). By mapping three of the fault systems, Taylor et al (2003) found average offsets in Tertiary thrusts and Palaeozoic-Mesozoic lithological units of only 12 km.…”
Section: Conjugate Strike-slip Faults Of Central Tibetmentioning
confidence: 99%
“…This pattern of faulting indicates a 250 km by 1500 km east-west-trending zone of conjugate strike-slip faulting across central Tibet that simultaneously accommodates north-south contraction and east-west extension (Taylor et al 2003). By mapping three of the fault systems, Taylor et al (2003) found average offsets in Tertiary thrusts and Palaeozoic-Mesozoic lithological units of only 12 km. This supports a model of coeval east-west extension and north-south contraction on multiple faults in a distributed pattern rather than the Qiangtang terrane behaving as a rigid block translating eastward, the latter requiring larger offsets on these faults.…”
Section: Conjugate Strike-slip Faults Of Central Tibetmentioning
confidence: 99%
See 3 more Smart Citations